Pengembangan Usaha Mikro Cilok di Desa Rumak, Kabupaten Lombok Barat - Endang Kartini; Nizar Hamdi; Ahmad Bairizki; Surahman Hidayat; Mustaan; Sigit Ary Wijayanto (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi AMM, 2024)
One of the micro businesses that was used as a target location was Cilok Abi, a micro culinary business owned by the local community. In this cilok business, several problems were found, including: Low understanding regarding the preparation of good financial reports and management of financial reports that is not yet optimal; Marketing capabilities are still conventional, so they have not been able to expand their market share; Limited labor both quantity and quality; The distribution permit number for the home food industry has not yet been registered. For this reason, the team provides business development assistance by: 1) training in simple financial management and bookkeeping; 2) Digital marketing training, 3) Training to manage and empower employees; and 4) Extension to obtain a home industry food production certificate (SPP-IRT).